A DFT investigation on the hydrodesulfurization mechanism of 4, 6-dimethyldibenzothiophene over different Ni-Mo-S active sites via different direct desulfurization pathways. (15th January 2022) - Zhou, Wenwu; Fan, Fei; Chen, Zhiping; Zhou, Anning; Zhang, Yating; Yao, Fei
Graphical abstract: Highlights: The DFT investigation on the DDS mechanism of 4, 6-DMDBT was performed. The ferromagnetism of Ni makes 4, 6-DMDBT undergo DDS reaction on the Ni-Mo-S edge site via Path 2 DDS mechanism. The ferromagnetism of Ni species lowered the needed activation energy on the corner active site. The ferromagnetism of Ni species makes 4, 6-DMDBT undergo DDS reaction via Path 1 DDS mechanism. The ferromagnetism has a crucial effect on the DDS of 4, 6-DMDBT on both kind of active sites. Abstract: The computational method based on the first principle of numerical atomic functions of density functional theory (DFT) was established to investigate the effects of ferromagnetism for the auxiliary Ni species on the direct desulfurization (DDS) mechanism of 4, 6-dimethydibenzothiophene (4, 6-DMDBT) hydrodesulfurization via two different reaction paths on both the corner active site and the edge active site. It is less likely for 4, 6-DMDBT undergoing the DDS reaction via both paths on the Ni-Mo-S edge active sites without considering the ferromagnetism due to the relative activation energy needed either for the cleavage of the first C–S bond or for the cleavage of the second C–S bond. However, 4, 6-DMDBT can undergo the DDS reaction via the Path 2 DDS mechanism in which the cleavage of the first C–S bond is the reaction rate control step. On the corner site, 4, 6-DMDBT inclines to undergo DDS via both the promoted paths and the cleavage of the first C–S bond is the reaction rate control step, the ferromagnetism of the Ni species lowered the activation energy for the reaction rate control step by approximately 4.8 kJ·mol −1 . The activation energy for the cleavage of the second C–S bond in the Path 1 DDS mechanism reduced from about 217.92 kJ·mol −1 to 112.32 kJ·mol −1 after taking the ferromagnetism of Ni species into account. Thus, the ferromagnetism of Ni species has a crucial effect on the DDS of 4, 6-DMDBT over both the corner active site and the Ni-Mo-S edge active site and should not be neglected.